Radiation sterilization of healthcare products - Głuszewski, Wojciech; P. Zagórski, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2003)
Basics of radiation chemistry of polymers are discussed, in particular the role of non-uniform distribution of energy in irradiated objects. The mechanisms of radiation-induced reactions start from two different origins: single-ionization spurs, and from multi-ionization spurs which are the cause of chain scission of polymers, with partial recovery as Y-crosslinks in polymers without steric hindrance. The main part (80%) of radiation energy is deposited as single ionization spurs leading to X-crosslinks. Both types of radiation-induced chemical effects are usually a positive phenomenon in radiation sterilization of medical devices made of polymers. The role of additives to polymer blends and copolymers is discussed in terms of energy transfer and biocompatibility. Forty years of experience with radiation sterilization of healthcare products have resulted in the formulation of many procedures. Authors have focused on the positive role played by basic research, which helps to limit the usual praxis of trial and error procedures in the selection of proper polymers for the manufacture of medical devices. Some remarks have been made in connection with terminology, which can avoid misunderstanding in dealing with producers of medical devices as well as end users of these products.